Beograd nekad i sad. - Van Woensel, Jan; Stamenkovic, Marko; Krivokapic, Jelena; Galerijia Beograd, Belgrado (Belgrade : Gallery Beograd, 2005)
Acostioaei, Dan ; Aires, Carlos ; Alvaer, Jesper ; Asselberghs, Herman ; Atay, Fikret ; Barich, Steven ; Bartana, Yael ; Bejenaru, Matei ; Biscotti, Rossella ; Blafield, Maija ; Brandt, Veronika ; Olger, Nils ; et al.
Servian and English texts
Galerija Beograd, Belgrado, september - october 2005
kunstcatalogus